2013
DOI: 10.1111/1750-3841.12049
|View full text |Cite
|
Sign up to set email alerts
|

Jujube Honey from China: Physicochemical Characteristics and Mineral Contents

Abstract: We investigated and compared the physicochemical properties (moisture, color, ash, pH, electrical conductivity, free acidity, lactonic acidity, total acidity, fructose, glucose, sucrose, diastase activity, and HMF) and mineral contents (Al, Ca, Co, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, As, Cd, Pb, and Zn), as well as total proline and total protein contents of 23 jujube honey samples collected from different regions of China. The mineral content was determined by inductively coupled plasma-optical emission spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
28
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 31 publications
(51 reference statements)
11
28
3
1
Order By: Relevance
“…In the present study, all samples had a percentage of moisture content below the imposed limit of ≤20%, the maximum acceptable moisture content of honey by the European Community Directive (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). The results presented herein are in accordance with those of other works (Can et al., ; Estevinho et al., ; Karabagias et al., ; Silva et al., , ; Zhou et al., ).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…In the present study, all samples had a percentage of moisture content below the imposed limit of ≤20%, the maximum acceptable moisture content of honey by the European Community Directive (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). The results presented herein are in accordance with those of other works (Can et al., ; Estevinho et al., ; Karabagias et al., ; Silva et al., , ; Zhou et al., ).…”
Section: Resultssupporting
confidence: 94%
“…All samples are below the maximum limit allowed (800 µs/cm) by Portuguese and European legislation (Ministry of Agriculture, Rural Development and Fisheries, ; Codex Alimentarius, ). These values are similar to those found in other studies (Belay et al., ; Karabagias et al., ; Louppis, Karabagias, Kontakos, Kontominas, & Papastephanou, ; Mondragón‐Cortez et al., ; Silva et al., ; Zhou et al., ). Several works reported that a linear relationship exists between the ash content and the electrical conductivity (Buba et al., ; Mondragón‐Cortez et al., ; Silva et al., , ).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…As the raw honey samples were collected from different locations, the variations of mineral element in honey depended on the type of soil in which the nectar-producing plants grow and on the vegetation conditions in the forage area (Pohl 2009). The potassium content of the raw honey samples was comparable to honeydew honey from Poland with 2641.9 mg/kg and honey from China with 1081.4 mg/kg (Chudzinska and Baralkiewicz 2010;Zhou et al 2013).…”
Section: Mineral and Heavy Metal Contentmentioning
confidence: 72%